Innovative demand feeding device using a light sensor - Mukai, Yukinori; Tan, Nai Han; Liau , Chung Fan (2012)
Demand feeding is a new feeding method by which fish can feed themselves. When fish require food, they switch on the feeding device. This method has several advantages, because the fish can eat feed, when they are most motivated to feed. Therefore, this method can thus minimize feed loss and reduce water pollution. We are conducting the feeding experiments using a commercialized demand feeding device that was imported from USA. Tiger grouper juveniles already remember the method to switch on the feeding device. Currently, we are getting data under project (SCF0068-AGR-2009 ). This device has a switch (a small target), and fish have to bite a target when they require food. During experiments, I noticed that we can use a light sensor (an infrared light beam sensor) instead of a switch (a small target). It means when the fish come to a location of a sensor, they interrupt a light beam. If the device is switched on by the interrupting light beams by the fish, the new device will work more smoothly for feeding themselves. We already made a prototype feeding devise using a light sensor. Fish could switch on more easily than the commercialized device.